Graphical analysis of photovoltaic generation and load matching in buildings: A novel way of studying self-consumption and self-sufficiency. (15th September 2019) - Luthander, Rasmus; Nilsson, Annica M.; Widén, Joakim; Åberg, Magnus
Highlights: Graphical approach to assess matching between photovoltaic electricity and loads. Combines the conventional measures self-sufficiency and self-consumption. Possible to visualize improved matching with energy storage and load shifting. Contribution of photovoltaic electricity for Swedish nearly zero energy buildings. Abstract: For on-site renewable energy supply, such as photovoltaic (PV) electricity generation, an important issue is the daily and seasonal matching between on-site supply and demand. The matching potential is frequently expressed using the load matching indicators such as self-sufficiency and self-consumption. This paper presents the Energy matching chart, which is a novel graphical approach to visualize the PV-load matching. The chart uses self-sufficiency and self-consumption to provide information regarding the matching in both size and time. Using the Energy matching chart, the matching between PV production and load presented in previous studies is graphically analyzed and compared. Furthermore, the potentials for the two most common measures for improving the matching, namely energy storage and load shifting, are investigated. The results show that energy storage has, on average, a significantly higher potential for increasing the PV-load matching than load shifting. The second part of the paper, illustrates the benefits of the Energy matching chart by evaluating the Swedish implementation of the EU legislation on nearly Zero Energy Buildings (nZEBs). The assessment is performed for detached houses and evaluates the feasibility to use PV and battery systems for Swedish nZEBs. The results show that on-site PV production can help buildings to meet the nZEB regulations, but there are limitations due to the poor time-dependent matching. With a combined PV-battery system, the potential to meet the regulation is significantly larger. To summarize, the Energy matching chart has the potential to become a useful tool in the assessment of PV system and the evaluation of load matching measures.